2010
DOI: 10.1007/s00795-009-0482-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression patterns of the tight junction-associated proteins occludin and claudins in secretory and mature ameloblasts in mouse incisor

Abstract: Tight junctions (TJs) function primarily as a barrier against paracellular transport between epithelial cells and are composed mainly of occludin (OLD) and claudins (CLDs). The CLD family consists of 24 members that show tissue- or cell-specific expression. Ameloblasts, which originate from the oral epithelium, form enamel, and enamel proteins and minerals are transported across the ameloblastic layer during amelogenesis. We immunohistochemically examined the distribution patterns of TJs in ameloblasts by obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 19 publications
5
21
2
Order By: Relevance
“…The similar results were observed by other groups2728293031. However, difference of the spatial and temporal distributions may be due to the animals used and tissue preparations as well as antibody concentrations and resources39. These data indicated that Klf5, Dspp and Dmp1 are involved in the odontoblastic differentiation and dentin formation.…”
Section: Discussionsupporting
confidence: 87%
“…The similar results were observed by other groups2728293031. However, difference of the spatial and temporal distributions may be due to the animals used and tissue preparations as well as antibody concentrations and resources39. These data indicated that Klf5, Dspp and Dmp1 are involved in the odontoblastic differentiation and dentin formation.…”
Section: Discussionsupporting
confidence: 87%
“…At the secretory stage, ameloblasts become postmitotic, polarise and develop secretory machinery. They are organised as a single-cell layer with well-defined proximal and distal cell-cell junctions 4. They secrete a set of mineral-binding peptides, forming an extracellular compartment of organic matrix (mainly amelogenins, enamelin and ameloblastin) 5.…”
Section: Introductionmentioning
confidence: 99%
“…TJ core components are claudins, a family of proteins that includes more than 24 peptides. To date, nine claudins have been identified in the dental epithelium of various animal species and humans 4 22–27…”
Section: Introductionmentioning
confidence: 99%
“…Expression of the TJ-associated proteins was clearly detected in odontoblasts, however, temporal and spatial distributions of these proteins such as Ocln in differentiating odontoblasts are different 48, 49, 5558 . The cause of the differences is still uncertain, and it may be due to the animals used and the methods for specimen preparation as well as antibody concentrations in each study 59 . Lee et al observed that Ocln and ZO-1 proteins are strongly expressed in odontoblasts at PNs from 7 to 18 examined in the wild type mouse teeth whereas expression of Ocln and ZO-1 is hardly detected in odontoblasts of Nfic-deficient mice at the same ages.…”
Section: Discussionmentioning
confidence: 99%